COVID-19 border policies create problems for African trade and economic pain for communities - Bouët, Antoine; Laborde Debucquet, David (International Food Policy Research Institute, 2020)
The COVID-19 pandemic has triggered a range of border controls in countries around the world to curb the spread of the disease. In Africa, these moves have interrupted progress toward economic integration. The African Continental Free Trade Area (AfCFTA), for example, was supposed to establish continentwide free movement of goods starting on July 1. Now, the African Union Commission has proposed postponing the launch until January 1, 2021. In addition, trade restrictions implemented in Africa and elsewhere in response to the pandemic are fueling fears of a new food crisis on the continent (see IFPRI’s tracking of export restrictions).